[OP.4A.03] IS WHITE COAT EFFECT "PROTECTIVE" FOR THE PROGNOSIS OF CARDIOVASCULAR EVENTS?. (September 2016) - Bastos, J.; Araújo, A.; Pires, J.; Pinto, J.; Almeida, P.; Polonia, J.
Abstract : Objective: Aim: It is not well known if systolic white coat effect (WCE), the difference between casual systolic blood pressure (SBPc) and daytime systolic blood pressure determined by ambulatory blood pressure (ABPM), is a marker or not of worst cardiovascular events (CV).The aim of the study was to evaluate the prognostic value of white coat effect in relation to cardiovascular events (CV) stroke (AVC) and coronary events (DC). Design and method: Casual and ABP were obtained in 1200 hypertensive patients (645 female) age 51 ± 12 years, BMI 27 ± 5 Kg/m2, SBPc 154.9 ± 20 mmHg, daytime SBP 137.7 ± 16 mmHg, WCE 8.6 ± 9 mmHg. Results: There were 133 deaths and 251 cardiovascular fatal and non-fatal events (147 strokes, 67 coronary events, 37 other CV events) during 21, 2 years of follow-up (mean 11, 8 ± 5, 1 years). Comparing those who have a positive WCE versus those who did not have, those who have WCE have significant less: BMI, 24 h, Daytime, nighttime systolic and diastolic blood pressure, 24 h, daytime, nighttime pulse pressure, ambulatory arterial stiffness index, less number of risk factor, ventricular cardiac mass but have higher prevalence of the female gender. When WCE was analyzed in a multivariate Cox after adjustment for age, BMI, gender, antihypertensive treatment and diabetes, those patients who have WCE has a negative correlation for global CV and stroke, respectively HR 0.67 (95% CI 0.46–0.98), HR 0.45 (95% CI 0.28–0.74) p < 0.05. In survival curves of Kaplan Meier free of events those who have WCE have less global CV(log Rank 4, 3 p < 0.05) and stroke (log Rank 5, 6 p < 0.02). Conclusions: In our population WCE seem to be "protective" of CV and stroke may be representing a " healthy" sympathetic autonomous system response.